Problems of research activity of medical college students (Pedagogy of Higher and Secondary Education, 2021)
We consider the definition of the «students research werk in in nursering», represent the principles of research study in Medical college, analize the level of interest and research activity.
Keywords: research activities; a student of medical college; research skills; research training; the nurs researches